What's your Finsta pare? analyzing the self-preservation of male Gen Z college students on their primary and secondary Instagram accounts - Rabena, Mikaehla Royo; Bautista, Roehl Niño (Quezon City University of the Philippines, Diliman, 2024)
Finstas or dump accounts as online intimate spaces may be seen as a strategic response to the pressure of conforming to social norms in front of a broad and vague online audience. Existing finsta research, however, has gathered data from a predominantly female respondent base. As a response, this research aimed to uncover the experiences of the minority of the practice– the male population, by analyzing how male Gen Z college students display their self-presentation in both their primary and secondary Instagram accounts. The analysis primarily focused on the general attitudes, emotions, and motivations, as well as the decision-making, creative, and thought processes of the users on self-presentation and curation online by examining their use, perception, and behavior in this reconfigured platform.

This study found that identities presented in the dump account are almost entirely opposite to their presented identities in the main account. Finstas serve nothing but the interest of its creator, thereby affording these users the freedom to share and document the messy and mundane aspects of their everyday life, allowing them to portray the most authentic self possible online. Such is the stark difference in their main accounts, where there is a constant pressure to look good and presentable. They are compelled to accommodate and account for a broader and vaguer audience, leading them to curate their identities to a more surface level and broad consumption-friendly version of themselves.
Thesis
Includes bibliography
Keywords: College students -- Online identities -- Philippines; Young men -- Social aspects -- Philippines; Social media -- College students -- Psychological aspects; Youth -- Online identities -- Social aspects; Online social networks